2023
DOI: 10.21203/rs.3.rs-2807625/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blockchain Enabled Decentralized Application for Securing Electronic Medical Records with Smart Contracts

Abstract: The Electronic Medical Records of patients maintained needs to be ensured that privacy is preserved and must be accessible to authorized users such as doctors. Most of the health care systems use the traditional centralized database platforms for these data management; which is neither secure nor easy to maintain. These platforms can be replaced by distributed, efficient, and much more secure platforms which are backed by blockchain technology. In this work, a Decentralized application (dApp) is developed whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Strict access control and privacy measures are essential so that only approved users can access EMRs [15]. Establishing public trust in EHR systems is critical, given concerns about security and data management [16]. Protecting health information needs attention by establishing standards like HIPAA [17].…”
Section: Lack Of Access Controls and Patient Privacymentioning
confidence: 99%
See 1 more Smart Citation
“…Strict access control and privacy measures are essential so that only approved users can access EMRs [15]. Establishing public trust in EHR systems is critical, given concerns about security and data management [16]. Protecting health information needs attention by establishing standards like HIPAA [17].…”
Section: Lack Of Access Controls and Patient Privacymentioning
confidence: 99%
“…Previous studies have demonstrated various inherent security threats to EMR and EHR systems. Respondents expressed concerns about the increasing number of cyberattacks on electronic medical records [10], [16]. A comprehensive survey of security and privacy challenges in modern healthcare analyzed potential attacks and defenses, emphasizing the need for further research to enhance healthcare technology security and privacy [32].…”
Section: Susceptibility To External Threatsmentioning
confidence: 99%